2018
DOI: 10.1111/pre.12361
|View full text |Cite
|
Sign up to set email alerts
|

Calcium carbonate productivity by Halimeda macroloba in the tropical intertidal ecosystem: The significant contributor to global carbonate budgets

Abstract: Halimeda is a potential carbon sink species and an important player in the global carbonate budget. The objectives of this study were to: (i) examine the CaCO 3 and sediment productions of H. macroloba by measuring the density, growth rate, and recruitment; (ii) quantify the numbers of aragonite crystals; (iii) document reproductive events; and (iv) determine the lifespan. This study was carried out at Lidee Lek Island, Satun, Thailand during July 2015 to April 2016. The density was measured using quadrats (0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 24 publications
1
24
1
Order By: Relevance
“…Tropical calcifying macroalgae, such as Halimeda spp., are already known for their potential role in climate change mitigation, as these macroalgae continue to exhibit high growth rates in reduced pH conditions (Kaewsrikhaw, Prathep, Darakrai, & Beer, ). Moreover, these macroalgae have the ability to contribute high amounts of carbonate to the ocean budgets, with annual production of 291.94–908.11 g/m 2 of CaCO 3 (Mayakun & Prathep, ), which supports the carbon sink via calcification. On the other hand, the high canopy complexity of Halimeda spp.…”
Section: Introductionmentioning
confidence: 99%
“…Tropical calcifying macroalgae, such as Halimeda spp., are already known for their potential role in climate change mitigation, as these macroalgae continue to exhibit high growth rates in reduced pH conditions (Kaewsrikhaw, Prathep, Darakrai, & Beer, ). Moreover, these macroalgae have the ability to contribute high amounts of carbonate to the ocean budgets, with annual production of 291.94–908.11 g/m 2 of CaCO 3 (Mayakun & Prathep, ), which supports the carbon sink via calcification. On the other hand, the high canopy complexity of Halimeda spp.…”
Section: Introductionmentioning
confidence: 99%
“…These two physical disturbances could explain the unexpectedly low growth and carbonate accumulation in Halimeda. Without seagrass competition, high sedimentation, and strong waves, Mayakun et al (2014) and Mayakun & Prathep (2019) showed much higher density, growth rate and CaCO 3 production of H. macroloba at Ko Mat Sum, in the Gulf of Thailand (with mean density of 11.70 ± 1.77 thalli m −2 ) and Lidee Island in the Andaman Sea (with mean density of 44.42 ± 13.95 thalli m −2 ), respectively.…”
Section: Discussionmentioning
confidence: 96%
“…In this study, four developmental stages were categorically defined in our H. macroloba samples as follows: stage 1: newly recruited plant; stage 2: young plant with 3-4 new segments and 1-2 levels of segment; stage 3: partially calcified plant with 3-4 levels of segment; and stage 4: mature calcified plant. We followed such developmental categorization according to the definition of Mayakun & Prathep (2019). Unfortunately, stage 5: fertile plant with reproductive cells and stage 6: dead plant, were rarely found and could not be collected.…”
Section: Segment Caco 3 Content and Number Of Aragonite Crystals Of Lmentioning
confidence: 99%
See 2 more Smart Citations